2019
DOI: 10.24059/olj.v13i4.1645
|View full text |Cite
|
Sign up to set email alerts
|

RE-EXAMINING & REPOSITIONING HIGHER EDUCATION: TWENTY ECONOMIC AND DEMOGRAPHIC FACTORS DRIVING ONLINE AND BLENDED PROGRAM ENROLLMENTS

Abstract: Economic and demographic shifts in the United State are transforming higher education. With substantial reductions in state funding, increasing campus energy and operational costs, endowments generating reduced returns, and a national economic readjustment of unprecedented proportions, higher education must re-examine and reposition itself to meet new and emerging challenges. This paper identifies ten economic factors and ten demographic factors that are confronting colleges and universities and driving online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…On-line education has become a viable option for non-traditional students who are working fulltime, unemployed and seeking employment, displaced or dislocated, have family responsibilities, or are unable to afford additional costs related to enrollment in traditional residential campuses (Betts et al, 2009). Karber (2003) suggested many opportunities for non-traditional education are accessible and available through the Internet and World Wide Web.…”
Section: Learning Styles Traditional and Online 131mentioning
confidence: 99%
“…On-line education has become a viable option for non-traditional students who are working fulltime, unemployed and seeking employment, displaced or dislocated, have family responsibilities, or are unable to afford additional costs related to enrollment in traditional residential campuses (Betts et al, 2009). Karber (2003) suggested many opportunities for non-traditional education are accessible and available through the Internet and World Wide Web.…”
Section: Learning Styles Traditional and Online 131mentioning
confidence: 99%
“…Therefore, PHEIs can meet students' specific needs through flexibility, customization, and assurance that the degree has value in the workforce. Additionally, the employment marketplace also demands higher levels of skills than ever before, leading to a continuous learning environment for today's workers (Betts et al, 2009;Chapman, 1986). PHEIs have new opportunities to consider with changing student, market, and economic demands.…”
Section: Students As Customersmentioning
confidence: 99%
“…Studies have shown that the future of HEIs is in mixing the two modes (Betts et al, 2009;. To achieve this, administrators of institutions implementing BL should routinize the assessment and evaluation of BL evaluation to measure achievements against targets and to provide feedback and feedforward to inform reviews in a meaningful and timely manner.…”
Section: F Assessment and Evaluationmentioning
confidence: 99%